2013
DOI: 10.1016/j.enconman.2013.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Performance of grid-tied PV facilities: A case study based on real data

Abstract: A new procedure is presented to analyse the performance of grid-tied PV facilities. It needs limited amounts of data that are easily sourced and is based on knowledge of the analyzed system and its mode of operation. The procedure is applied, in a case study, to compare real PV production at two 100 kWp grid-connected PV installations. Located in the same geographical region, the installation of these two facilities followed the same construction criteria -PV panels, panel support system and wiring-and the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The PVPS Task 2 provided suitable information on the operational performance, reliability, and costs of PV systems to various stakeholders. In addition, over the previous years, several groups of researchers conducted a performance evaluation of small and utility-scale PV projects [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. The performance of PV projects are essentially analyzed in terms of a) capacity utilization factor, b) specific energy generation, c) performance ratio, d) efficiency of the PV system, and e) levelized cost of electricity.…”
Section: Mwmentioning
confidence: 99%
“…The PVPS Task 2 provided suitable information on the operational performance, reliability, and costs of PV systems to various stakeholders. In addition, over the previous years, several groups of researchers conducted a performance evaluation of small and utility-scale PV projects [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. The performance of PV projects are essentially analyzed in terms of a) capacity utilization factor, b) specific energy generation, c) performance ratio, d) efficiency of the PV system, and e) levelized cost of electricity.…”
Section: Mwmentioning
confidence: 99%
“…The mean value of PR is 78%. As a comparison, values of PR between 48% and 93% have been reported in other works (Munro and Blaesser, 1994;Anis and Nour, 1995;Baltus et al, 1997;Blaesser, 1997;Decker and Jahn, 1997;Erge et al, 2001;Oozeki et al, 2010;Reich et al, 2012;Van Sark et al, 2012, Pelland andAbboud, 2008;Ueda et al, 2009;Eltawil and Zhao, 2010;Hussin et al, 2012;Wittkopf et al, 2012;Díez-Mediavilla et al, 2013;Woyte et al, 2013;Bonsignore et al, 2014;Colantuono et al, 2014;Myong et al, 2015;Tsafarakis and Van Sark, 2015;Kausika et al, 2018;Seme et al, 2019).…”
Section: C) Technical Qualitysupporting
confidence: 57%
“…Over the last decades, numerous monitoring campaigns have allowed to report and analyse the performance of thousands of PV systems worldwide (Anis and Nour, 1995;Baltus et al, 1997;Blaesser, 1997;Decker and Jahn, 1997;Erge et al, 2001;Pelland and Abboud, 2008;Ueda et al, 2009;Eltawil and Zhao, 2010;Hussin et al, 2012;Leloux et al, 2012aLeloux et al, , 2012bWittkopf et al, 2012;Díez-Mediavilla et al, 2013;Woyte et al, 2013;Bonsignore et al, 2014;Colantuono et al, 2014;Leloux et al, 2015;Myong et al, 2015;Taylor et al, 2015a;Tsafarakis and Van Sark, 2015;Kausika et al, 2018;Seme et al, 2019). These studies have shown a wide disparity in performance between the PV systems, with Performance Ratio (PR) values typically comprised between 60% and 90%.…”
Section: Introductionmentioning
confidence: 99%
“…itoring and performance evaluation of the PV systems are necessary [4]- [6]. At present, many performance evaluation methods of PV systems have been presented.…”
Section: Introductionmentioning
confidence: 99%